Case on Customized Logistics Services - Siti Afiqah, Kamaruzaman (Penerbit UMP, 2017)
Layout decision and inventory management is interlinked between each other as accurate layout decision will be beneficial to a business in managing their inventories. Layout is one of the crucial decisions that determine the long-run efficiency of operations. Layout has strategic since it starts an organization’s competitive priorities in regard to processes, capacity, cost, and flexibility as well as quality of work life, contact, customer and image.